Modelagem e análise de confiabilidade de manipuladores com elos flexíveis - Sandrini, Marina (2023)
This master’s dissertation presents an approach based on the stochastic method of finite elements with the Lagrange principle. This was done to obtain the dynamic model of manipulators with them flexible and uncertain model parameters of flexible arms, such as force. In this sense, the present work allowed the analysis of the dynamic response of the flexible manipulators with intermittents in terms of response in the time domain and in the frequency domain. The reliability analysis allowed evaluating the effect of parametric uncertainties on residual vibrations. Numerical methods based on first-order reliability were analyzed to understand whether used in conjunction with the formulation of the dynamic model based on stochastic finite elements, they become adequate. The results found validate the studied methodology and propose the application of future work in the scope of optimal design and control.